The hydrogen peroxide-sensitive proteome of the chloroplast in vitro and in vivo - Muthuramalingam, Meenakumari; Matros, Andrea; Scheibe, Renate; Mock, Hans-Peter; Dietz, Karl-Josef (Frontiers in Plant Science, 2013)
Hydrogen peroxide (H2O2) evolves during cellular metabolism and accumulates under various stresses causing serious redox imbalances. Many proteomics studies aiming to identify proteins sensitive to H2O2 used concentrations that were above the physiological range. Here the chloroplast proteins were subjected to partial oxidation by exogenous addition of H2O2 equivalent to 10% of available protein thiols which allowed for the identification of the primary targets of oxidation. The chosen redox proteomic approach employed differential labeling of non-oxidized and oxidized thiols using sequential alkylation with N-ethylmaleimide and biotin maleimide. The in vitro identified proteins are involved in carbohydrate metabolism, photosynthesis, redox homeostasis, and nitrogen assimilation. By using methyl viologen that induces oxidative stress in vivo, mostly the same primary targets of oxidation were identified and several oxidation sites were annotated. Ribulose-1,5-bisphosphate (RubisCO) was a primary oxidation target. Due to its high abundance, RubisCO is suggested to act as a chloroplast redox buffer to maintain a suitable redox state, even in the presence of increased reactive oxygen species release. 2-cysteine peroxiredoxins (2-Cys Prx) undergo redox-dependent modifications and play important roles in antioxidant defense and signaling. The identification of 2-Cys Prx was expected based on its high affinity to H2O2 and is considered as a proof of concept for the approach. Targets of Trx, such as phosphoribulokinase, glyceraldehyde-3-phosphate dehydrogenase, transketolase, and sedoheptulose-1,7-bisphosphatase have at least one regulatory disulfide bridge which supports the conclusion that the identified proteins undergo reversible thiol oxidation. In conclusion, the presented approach enabled the identification of early targets of H2O2 oxidation within the cellular proteome under physiological experimental conditions.